Rancang bangun sistem monitoring ruang server berbasis Internet of Things (IoT) menggunakan thingspeak dan notifikasi telegram - Khoir, Akiful (Maliki Interdisciplinary Journal, 2024)
Server room has a very important role for an agency or company because server space is useful for storing data on server devices. In this research, a tool was designed that can monitor the temperature and humidity of the server room. Apart from that, it also adds smoke and fire detection. The sensors used are the DHT 22 sensor, MQ-2 sensor, and fire sensor. Data will be displayed on the LCD and also Thingspeak. Reading and sending sensor data using Arduino Nano and NodeMCU ESP8266. Finally, notifications were designed if conditions were above the normal threshold via the Telegram application and also a buzzer. The DHT22 sensor shows a different value from the sensor in the server room with a difference of 1°C to 2°C. . The MQ-2 sensor reading shows a value of 0 when there is no fire or smoke. When fire or smoke is approached, the sensor value immediately rises quickly beyond 1000. The fire sensor is tested by bringing the flame closer to the sensor. When the sensor is brought close to a fire, the LED on the sensor will light up and the sensor reading shows the number 1. The tool has been successfully tested and is being used properly. The sensors used display good results and the data is successfully displayed on the LCD and Thingspeak. Likewise, notifications on the Telegram application and buzzer work well.